The Effects of Incomplete Outcome Feedback on Auditors' Self-Perceptions of Judgment Ability - Waller, William S.; Felix, William L. (The Accounting Review, 1984)
[Auditors' self-perceptions of their judgment ability may affect how well they learn from experience and how much they rely on decision aids. This study tests the hypothesis that incomplete outcome feedback causes auditors' self-perceived judgment ability to be affected by factors that are not necessarily related to actual judgment ability. The results of an experiment that used professional auditors as subjects making internal control judgments were, for the most part, consistent with this hypothesis.]